Toward Multi-Scale Computational Modeling in Developmental Disability Research - Dammann, O.; Follett, P. (Neuropediatrics, 2011)
The field of theoretical neuroscience is gaining increasing recognition. Virtually all areas of neuroscience offer potential linkage points for computational work. In developmental neuroscience, main areas of research are neural development and connectivity, and connectionist modeling of cognitive development. In this paper, we suggest that computational models can be helpful tools for understanding the pathogenesis and consequences of perinatal brain damage and subsequent developmental disability. In particular, designing multi-scale computational models should be considered by developmental neuroscientists interested in helping reduce the risk for developmental disabilities.
Keywords: developmental disability; computational modeling; theoretical neuroscience